KECENDERUNGAN ANAK MENJADI PELAKU DAN KORBAN BULLYING DITINJAU DARI KUALITAS KELEKATAN DENGAN IBU YANG BEKERJA - Sri Wahyuni & Yulita Kurniawaty Asra (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
Bullying has become a serious problem in schools and occurs in all countries. The purpose of this study is to see the tendency of children to be actors and victims of bullying in terms of quality of attachment with working mothers. The subjects were 336 students (175 male and 161 female) who have working mothers. The results showed that students who have a low quality of attachment with the mother who works has the tendency to be actors and victims of bullying than students who have a high attachment quality. Students in higher classes tend to bullying than students in lower grade, and boys were also higher tendency to bullying than girls. For mothers working hours, there was no difference in bullying behavior. While the tendency to be a victim, there is no difference based on class and gender. However, mothers who have longer working hours make children easily become victims of bullying